Relevansi Manusia Dengan Pendidikan - Julhamdani, Feri; ., Karman; Nugraha, Heryana; Trianti, Elis (CV. ITTC INDONESIA, 2023)
This research explores the relevance of humans to education to understand how Islamic teachings view the relationship between individual humans and the education system. This research identifies the values, principles and goals of education in Islam related to human development. Literature findings also highlight the concept of lifelong learning and self-improvement efforts as an integral part of Islamic teachings. This research explores how education can play a role in shaping moral and spiritual character, as well as preparing individuals to contribute positively to society in accordance with Islamic values. This research provides a valuable conceptual contribution to the development of education that is more holistic and in accordance with Islamic principles.